Design aspects and probabilistic approach for generation reliability evaluation of MWW based micro-hydro power plant - Saket R.K. (My University, 2025)
This paper presents the design aspects and probabilistic approach for the generation reliability evaluation of an alternative resource: municipal waste water (MWW) based micro-hydro power plant (MHPP). Annual and daily flow duration curves have been obtained for design, installation, development, scientific analysis and reliability evaluation of the MHPP. The hydro-potential of the waste water flowing through sewage system of Brocha sewage plant of the Banaras Hindu University campus is determined to produce annual flow duration and daily flow duration curves by ordering the recorded water flows from maximum to minimum values. Design pressure, roughness of the pipe's interior surface, method of joining, weight, ease of installation, accessibility to the sewage system, design life, maintenance, weather conditions, availability of material, related cost and likelihood of structural damage have been considered for the design of a particular penstock for reliable operation of the developed MHPP. MWW and self-excited induction generator (SEIG) based MHPP is developed and practically implemented to provide reliable electric power to charge the battery bank. Generation reliability evaluation of the developed MHPP using the Gaussian distribution approach, safety factor concept, peak load consideration and Simpson 1/3rd rule has been presented in this paper. © 2013 Elsevier Ltd.